2012
DOI: 10.1371/journal.pone.0033675
|View full text |Cite
|
Sign up to set email alerts
|

DEAD-Box Protein Ddx46 Is Required for the Development of the Digestive Organs and Brain in Zebrafish

Abstract: Spatially and temporally controlled gene expression, including transcription, several mRNA processing steps, and the export of mature mRNA to the cytoplasm, is essential for developmental processes. It is well known that RNA helicases of the DExD/H-box protein family are involved in these gene expression processes, including transcription, pre-mRNA splicing, and rRNA biogenesis. Although one DExD/H-box protein, Prp5, a homologue of vertebrate Ddx46, has been shown to play important roles in pre-mRNA splicing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…Our previous study has shown that Ddx46, a member of the DEAD-box RNA helicase family, is required for the development of digestive organs and the brain, possibly by regulating pre-mRNA splicing [20]. Here, we show zebrafish Ddx46 expression in HSCs during development.…”
supporting
confidence: 48%
See 4 more Smart Citations
“…Our previous study has shown that Ddx46, a member of the DEAD-box RNA helicase family, is required for the development of digestive organs and the brain, possibly by regulating pre-mRNA splicing [20]. Here, we show zebrafish Ddx46 expression in HSCs during development.…”
supporting
confidence: 48%
“…We have previously shown that Ddx46 hi2137/hi2137 mutants have defects in the formation of digestive organs and the brain [20]. In the course of the phenotypic analyses of Ddx46 hi2137/ hi2137 mutants, we also found that the expression of hematopoietic markers was downregulated in the mutants.…”
Section: Ddx46mentioning
confidence: 72%
See 3 more Smart Citations